The Effect of Content Marketing and Online Customer Reviews on Purchase Intention Through Customer Trust as an Intervening Variable on Food and Beverage Products in Mojokerto - Renanda Auresty Faradita; Nurhadi Nurhadi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to determine the effect of content marketing on online customer reviews on purchase intention through customer trust in followers of the @kulineran.mjk Instagram account. This type of research is associative quantitative research with the method of Partial Least Square analysis technique with smartPLS 4.0 software. The number of samples was 160 respondents using the Slovin formula and the method of drawing samples with non-probability sampling, namely with purposive sampling technique. Data collection by questionnaire via direct message. Based on the research that has been done, the results show that content marketing has a significant effect on customer trust, online customer review has a significant effect on customer trust, customer trust has a significant effect on purchase intention, content marketing has a significant effect on purchase intention, online customer review has a significant effect on purchase intention through customer trust, online customer review has a significant effect on purchase intention through customer trust